Chromatographic and mass spectrometric fingerprinting analyses of Angelica sinensis (Oliv.) Diels-derived dietary supplements - Zhao, Yang (2013)
Angelica sinensis (Oliv.) Diels (“Danggui” in Chinese) is one of the most commonly used Traditional Chinese Medicines (TCMs). It has been used to invigorate blood circulation for the treatment of anemia, hypertension, chronic bronchitis, asthma, rheumatism and cardiovascular diseases. There are a number of A. sinensis-derived dietary supplements in the U. S. markets. However, no study has been conducted to investigate the quality of these dietary supplements. In this paper, high-performance liquid chromatographic and flow-injection mass spectrometric fingerprints were both evaluated to assess the consistency of A. sinensis-derived dietary supplements. Similarity analysis was carried out on the high-performance liquid chromatographic (HPLC) fingerprints. Meanwhile, principal component analysis (PCA) was performed on the data obtained from flow-injection mass spectrometric (FIMS) fingerprints, which cananalyze each sample in 2 min, compared to 30 min required for the chromatographic fingerprint. Principal component analysis (PCA) of the FIMS fingerprints was performed. Both methods show significant chemical differences between samples that may be due to differences in growing locations, growing conditions, harvesting times, and/or botanical processing. The loading plots obtained from PCA singled out the discriminatory ions that were responsible for chemical differences of A. sinensis-derived dietary supplements.